2016
DOI: 10.1371/journal.pone.0153250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bristle Stiffness of Manual Toothbrushes on Eroded and Sound Human Dentin – An In Vitro Study

Abstract: AimThe aim of this study was to determine the influence of manual toothbrushes with different bristle stiffness on the abrasivity on eroded and sound human dentin.Materials and MethodsDentin specimens were made from impacted third molars and attributed to three groups: erosion-abrasion (EA), abrasion (A) and erosion (E). The specimens from EA and E were treated with 1% citric acid (pH 2.3) for 1 min rinsed, and neutralized with artificial saliva for 15 min. This cycle was repeated five times. Thereafter, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
3
35
2
3
Order By: Relevance
“…In two previous studies of similar design 15,16 , wear of eroded dentin increased with decreasing filament diameter. However, the present data suggests that filament stiffness is likely to be a secondary factor in wear of eroded dentin, behind abrasivity.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…In two previous studies of similar design 15,16 , wear of eroded dentin increased with decreasing filament diameter. However, the present data suggests that filament stiffness is likely to be a secondary factor in wear of eroded dentin, behind abrasivity.…”
mentioning
confidence: 68%
“…It is often postulated that hard toothbrushes cause more wear than soft ones which has led to recommendations 4 of soft toothbrushes for patients diagnosed with erosive tooth wear 18,19 . Mechanistic laboratory studies, however, revealed the opposite as soft toothbrushes were found to accelerate the wear process because of their greater ability to carry abrasive particles across the surface 13,15,16 . Nonetheless, these studies were somewhat limited in their approach as acid challenges were mimicking intrinsic erosion 13,15 or abrasion periods were too long 16 , therefore likely exaggerating effects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations